Harjaantumisoppilas peruskoulun liikuntakasvatuksessa - Niemelä, Eino (1991)
The aim of this study was to develop the physical education possibilities of trainable mentally retarded pupils by examining their attainment of physical education objectives, the factors accounting for the successful attainment of those objectives, .and the effects on such pupils of an intensive physical exercise programme on their physical functional capacity and maladaptive behavior. A sample of 156 trainable mentally retarded children from the provinces of Central Finland, Oulu and Uusimaa were selected for the study. The objectives were set according to criteria drawn from the comprehensive school physical education curriculum. The pupil, educational conditions and teacher variables assessing the attainment of the objectives were measured by means of sum variables the components of which were selected according to the theoretical background of the study. For the experimental the study the 57 subjects from Central Finland were randomly assigned into experimental and control groups. The intensive physical exercise programme comprised 21 indoor jogging bouts of 20 minutes duration and 7 outdoor jogging bouts lasting one hour each. The results showed that the skills involved in playing ball games, athletics, winter sports and swimming proved the most difficult to learn. Factor analysis enabled physical education to be divided into the following areas - motor skills, movement to music and games of movement, outdoor activities, physical fitness, and self-concept in relation to physical exercise. The differences between the sexes in attaining the physical education objectives were insignificant. Statistically significant differences were, however, found between primary, junior and senior levels. Regression analysis supported Bloom's theory that learning results are best explained by pupil variables. The intensive physical exercise programme produced statistically significant improvement in physical functional capacity, but only a .05 level change in maladaptive behavior. By the end of the follow-up the differences between the experimental and control groups had considerably decreased in both physical functional capacity and maladaptive behavior.